A review of ex-mining land reclamation as construction project activities : focusing in City of Ipoh / Mohd Najib Abd Rashid ... [et al.] - Mohd Najib, Abd Rashid; Hayroman, Ahmad; Siti Jamiah, Tun Jamil; Noor Azam, Yahaya; Mohamad Hamdan, Othman (2015)
A large demand of housing and land development in Malaysia since the last two decades has resulted in the reduction of suitable and proper spot for housing development. This kind of land can now only be found in the area far away from the cities. However, most people choose to be near or not too far from the cities. This has led to the development of the less desirable area such as ex-mining land.A study of completed and ongoing development in the above mentioned areas reveal that there are less than adequate guidelines, laws or policies to ensure development in these areas are given proper attention in term of safety and environmental provisions. This paper discussed several issues regarding to the construction of housing and development in the difficult and less desirable areas.As land is getting scarce due to rapid development, an abandoned ex-mining area hasbecome valuable lands for developments.